Investigation of pre-treatment used for organic foulant removal from wastewater effluent on fouling of membranes used for wastewater treatment and reuse - Aryal, Ashok (Curtin University, 2009)
The volume of global water is very large. However, the source of water on the globe is finite and also distributed in quite uneven manner. In addition to this, freshwater source is dwindling and becoming scarce from human intervention including anthropogenic input, reduced rainfall due to climate change and increased water demand for drinking, hydropower, irrigation and industrial use combine with increasing pollution load from urban, industrial and agricultural discharges. This results many part of the world with only limited or no fresh water source to meet the increasing water demand. So, development of alternative water resource such as wastewater recycling is highly essential to face the degradation of and shortage of water. In this context, the use of membranes in wastewater reuse process is likely to play an important role to combat the potential degradation and shortage of the water resources as well as to meet increasingly stringent standards in terms of potable and industrial use. It has been used for the treatment of wastewater effluent at Beenyup and Kwinana wastewater treatment plant by Water Corporation. While Beenyup will recycle water to recharge the aquifer for future use, Kwinana plant recycles it for industrial use. Despite various promises of membrane, the wide application is still limited as both plants experienced membrane fouling particularly organic and biofouling leading to increase in operation cost.Organic foulants could cause both reversible and irreversible fouling. While reversible fouling can be overcome by backwashing, irreversible fouling tenders expensive membranes useless. So, this research aimed to investigate the in-depth assessment of organic matter removal particularly focusing on pretreatment side to reduce the fouling rate by minimizing the organic material prior to the membrane filtration. Two fundamental mechanism particularly physicochemical and biological processes were investigated both separately and in combination in this research. They were analysed in terms of organic matter removal (DOC, UV254, SUVA, Turbidity,… etc) during the study of these process. Enhanced coagulation by Ferric Chloride and MIEX® were studied as physico chemical process while BAC was studied as biological treatment process for various experimental configurations. The laboratory results showed that physio chemical process can achieve around 60 percent removal of organic carbon present in the wastewater. Similarly, biological process was also found to be effective and achieved up to 45 percent removal of organic carbon. The combined performance of pre-treatment particularly BAC followed by the coagulation was also investigated and found to be more effective as BAC converted nonsorbable organic carbon to sorbable organic carbon by increasing the efficiency of coagulant significantly.This combination achieved the removal of organic carbon even up to 90 percent. This means, fouling of membrane can be reduced significantly by applying fore mentioned treatment individually or in combination. However, to understand the fouling mechanism further, more detail laboratory works need to be done. So, various pre-treated secondary wastewater needs to be brought into membrane fouling experiments in the next stage of research in order to understand the insight of membrane fouling and its minimization to make the membrane technology economical for the reuse of wastewater.